Efeitos gastroprotetor e procinético do sulfeto de hidrogênio (H2S) em camundongos : papel dos neurônios aferentes sensíveis a capsaicina, receptores vanilóides do tipo 1 (TRPV1) e canais de K ATP-depedentes (KATP) - Medeiros, Jand-Venes Rolim (2009)
Recently, the involvement of H2S has been demonstrated in several physiological and pathological conditions, being constitutively produced in mammalian tissues. AIM: To study the role of H2S on both the gastric mucosa defense and the control of gastric motility in mice, and additionally to evaluate the participation of KATP channels, capsaicin-sensitive afferent neurons and TRPV1 receptors in these effects. METHODS: Swiss mice were pre-treated with either L-cysteine (25, 50 or 100 mg/kg, p.o), NaHS (75, 150 or 300 µmol/kg, p.o) or Lawesson´s reagent (3, 9, 27 or 81 µmol/kg, p.o). The animals were then given ethanol 50% (0.5ml/25g, p.o.) 30 min later. After 1h of ethanol instillation, the mice were sacrificed and had the stomach collected to measure the injured area through planimetry software. Moreover some samples were obtained to histopathological analysis, glutathione (GSH), and malonyldialdehyde (MDA) dosages. In the study of gastric empty, the animals were administered L-cysteine, NaHS or Lawesson´s reagent, and 30 min later a phenol red solution (0.75 mg/ml) diluted in glucose (5%) was also given. The sacrifice was performed 10, 20 or 30 min after the latter to determine in a spectrophotometer the gastric empty. In another experimental setting, glibenclamide (3 or 10 mg/Kg, v.o.) or capsazepine (10 mg/kg, i.p) were injected 1h previously to the L-cysteine (50 mg/kg, p.o) or H2S donors (NaHS 150 µmol/kg or Lawesson´s reagent 27µmol/kg, p.o) instillation. In order to study the role of capsaicin-sensitive afferent neurons, high neurotoxic doses of capsaicin was instilled into the animals. On the 8th day post capsaicin injection, NaHS or Lawesson´s reagent was administered. The protocol for ethanol administration, sacrifice, and dosages were repeated for these conditions as described previously. Finally, the spontaneous contraction of isolated gastric fundus to KCl (control contraction) and growing doses of NaHS was determined in vitro through and isometric force transducer connected to an acquisition system. RESULTS: L-cysteine, NaHS and Lawesson´s reagent prevented, in a dose dependent manner, the ethanol-induced gastric injury. Besides, high and low levels of GSH and MDA were found respectively in comparison to the control group given only ethanol. Glibenclamide (10 mg/kg) and capsazepine completely reversed the protective effect of the H2S donors. The animals that undergone afferent neuronal ablation also developed gastric lesions despite the injection of L-cysteine and H2S donors. NaHS, Lawesson´s reagent and L-cysteine all accelerated gastric empty in comparison to the control group and in a dose-dependent manner. Such prokinetic effect was abolished in glibenclamide and capsazepine pre-treated mice. The NaHS was also able to induce an increase in gastric fundus basal tonus in vitro presenting a ceiling effect in the concentration of 300µM when compared with the standard KCl contraction. CONCLUSIONS: The H2S prevented the ethanol-induced gastric damage, GSH consumption, and lipid peroxidation processes in the stomach mucosa of mice. The H2S also revealed a prokinetic effect leading to a higher liquid gastric empty in mice. Such results seem to be dependent on KATP channels, sensory afferent neurons, and TRPV1 receptors activation.